2011
DOI: 10.1007/s13197-011-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antifungal hot-water treatments on papaya postharvest quality and activity of pectinmethylesterase and polygalacturonase

Abstract: The effect of antifungal hot-water treatments (AHWT) at 55°C for 0, 3, 6 and 9 min on quality attributes and cell-wall enzymatic activity during storage at 25°C was investigated in papaya fruit. The total soluble solids (TSS), pH, titratable acidity (TA), firmness and fresh weight loss were not affected, whereas color on skin was negatively affected by the treatments of 6-and 9-min. However, the skin color was not different between the 3-min treated fruit and the untreated fruit during the storage. Decay was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
(26 reference statements)
3
18
0
Order By: Relevance
“…According to the same authors, the carbon necessary for the synthesis of sucrose originated from the cell wall (30 % cellulose, 30 % hemycellulose, 25 % pectin, and 5 % proteins). Other studies showed a decrease of galactose and an increase of glucose due to the degalactosylation of polysaccharide chains in apples, strawberries, tomatoes, and in germinating seeds (Ignacio et al 2011;Brett and Waldron 1996;Pressey 1983). This rapid metabolization of galactose explains why Gomez et al (2002) did not find free galactose in ripped papayas.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to the same authors, the carbon necessary for the synthesis of sucrose originated from the cell wall (30 % cellulose, 30 % hemycellulose, 25 % pectin, and 5 % proteins). Other studies showed a decrease of galactose and an increase of glucose due to the degalactosylation of polysaccharide chains in apples, strawberries, tomatoes, and in germinating seeds (Ignacio et al 2011;Brett and Waldron 1996;Pressey 1983). This rapid metabolization of galactose explains why Gomez et al (2002) did not find free galactose in ripped papayas.…”
Section: Resultsmentioning
confidence: 92%
“…Ohtani and Misaki (1983) showed that the seeds of Carica papaya L. exhibited a high level of α-D-galactosidase and α-D-mannosidase activities. Other studies indicated that cellulase activities increase during the maturation of avocados, peaches, strawberries, tomatoes, and papayas (Ignacio et al 2011;Awad and Young 1979;Hobson 1981;Paull and Chen 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The delay of ripening, senescence, and the degradation of antifungal compounds might occur during the application of HW; moreover. it could control the activity of pectinmethylesterase and polygalacturonase (Chávez-Sánchez et al, 2013). Treatment of this type associated with Rhodotorula glutinis was shown to reduce blue mold (Penicillium espansum) in pears, where fruits treated for 15 min for 46°C showed a lower incidence of this disease (Zhang et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrothermal treatments have been shown to be effective as a nonchemical alternative to improve the postharvest quality of several horticultural products. These treatments may affect ripening and protect against physiological disorders, but they have also been effective for decay control (Chávez‐Sánchez and others ). Chitosan is a natural polysaccharide that has a huge variety of useful physicochemical and biological properties, such as nontoxicity for the human organism, and chelating, biocompatible, biodegradable, and film‐forming ability, as well as antimicrobial activity against a wide variety of microorganisms (Erben and others ).…”
Section: Introductionmentioning
confidence: 99%